The Basics of Child Personality Development (Study of Analysis of Surah al-A'raf Verses 31-33 in Tafsir Ash-Shawi) - M. Nasir; Samwil Samwil; Muhibbul Subhi (International Journal of Ethno-Sciences and Education Research, 2022)
Al-Qur'an is the word of Allah SWT which contains various kinds of rules, guidelines for human life that governs every aspect of life, including the child's personality. One of the surahs that talk about children is Surah Al-A'raf verses 31-33, In that verse, Allah SWT gives an illustration to believers about how to dress, drink, and do evil deeds. Concerning this verse, Ash-Shawi provides an in-depth understanding of how to dress, eat and drink permitted by the Law. This discussion aims to find out the interpretation of Surah Al-A'raf verses 31-33 in the Ash-Shawi's interpretation related to personality and to figure out the educational values emphasized in the verse. The writer uses a literature study as a data collection technique. The child's personality is determined by Islamic education in the family. This is obtained by nurturing and guiding because the children were born in a state of nature that requires guidance and direction to develop their potential.